Pendampingan Belajar Baca Qur’an Anak-Anak TPA An-Najiyah Desa Sindang Agung - Elfina, Nisa; Musyaddad, Anwar (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
The aim of holding community service in the form of assistance activities in learning to read the Al-Qur'an for children at An-Najiyah TPA is to provide assistance in reading the Al-Qur'an with the correct legal rules for reading for children at An-Najiyah TPA located in the village. Sindang Agung. This service activity is part of STAI Ibnu Rushd's KKN student activities while carrying out KKN in Sindang Agung Village. The method of implementing this service is carried out using PAR work (Participatory Action Reseach) namely service research activities in which the author is directly involved in a participatory manner as a supervisor at the service location. The place where this service activity is carried out is An-Najiyah TPA which is located in Sindang Sari Hamlet, Sindang Agung Village, Tanjung Raja District, North Lampung Regency with an implementation time of 7 days from 09 to 16 August 2023 at 16:00 WIB. The results of this service show that with assistance in learning to read the Al-Qur'an correctly by STAI Ibnu Rushd Kotabumi KKN students, the children become more enthusiastic about learning so that the children's ability to read the Al-Qur'an increases, besides that the children -Children also have a better understanding of the science of recitation after following the program that has been implemented.